(untitled) (Religious dialogue and cooperation, 2024)
The Bahá’í faith derives from Babì movement and takes its first steps in Persia during the first half of the 19th century. Bahà’u’llàh reveals to be the new Manifestation of God in 1863. Thanks to his successors, the Bahá’í faith transcended its geographical boundaries, initially Persian and Arab, by embracing Western Countries and adapting its characteristics to those cultural contexts. Commencing from my doctoral project, the contribution aims to focus on the presence of the Bahá’í religious minority in Tunisia, which arrived in the 1920s of the 20th century. The Country, in addition to the Bahá’í one, welcomes the Shiite Muslim minority, as well as various Christians, which can be categorized as indigenous (converted Tunisians), European, Sub-Saharan, and the Jew minority. The presence of the Bahá’í community, as reported by the Association of Religious Data Archives (ARDA), is estimated to be around 2,000 believers, however, it appears to engage in a fluid coexistence with other religions and navigate a cold conflict within a predominantly Sunni Muslim context. The oral testimonies range from examples of “peaceful coexistence” to “fear of openly declaring oneself”. Moreover, they reveal that the number of believers ranges between 200 and 250, as many believers do not officially declare their affiliation.Prior to the Revolution in 2011, nobody dared to openly acknowledge their affiliation with the Bahá’í faith; subsequently, thanks to a newfound spirit that has animated religious, national, and ethnic minorities (including Berber and Black communities) – Bahá’í adherents have reported an increased sense of freedom of expression. However, instances of believers experiencing apprehension regarding potential acts of violence and discrimination persist.